The textbook as a major source of difficulty in the teaching and learning of geography through the medium of English in Standard 3 in black primary schools - Langhan, David Patrick (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1991)
This dissertation provides evidence to suggest that teaching/learning difficulties with geography in Std 3 are largely attributable to textbooks which fail as well constructed discourse and include uninterpretable illustrations. The discourse properties most likely to affect the readability of textbooks intended for ESL/EFL pupils are identified. Selected passages from two widely used Std 3 geography textbooks are analysed in terms of these properties, and are shown to fail extensively as well constructed discourse. Following classroom observation and informal interviews which confirmed the inappropriacy of the texts for Std 3 pupils, the passages were re-written, following the necessary properties of well constructed expository discourse. The readability of these two sets of texts was then tested on a group of nine Std 3 teachers in two structured interviews. The findings reveal that the re-written passages are significantly more readable than the textbook passages. Recommendations that affect education authorities, curriculum designers, syllabus makers, textbook authors, publishers and teacher training colleges are provided
Keywords: Children, Black -- Education -- South Africa; Geography -- Textbooks; Geography -- Study and teaching (Primary) -- South Africa; Language and education -- South Africa